The Organ Donor Experience: Good Samaritans and the Meaning of Altruism - Bramstedt, Katrina A. (Rowman & Littlefield Publishers, 2011)
With a current US need of over 115,000 organs one would think that Good Samaritan donors would be welcomed with open arms by transplant centers and society in general; however, this is often not the case. Tell someone that you have donated an organ to a stranger and the reaction is likely to be one of astonishment and disbelief. Some doctors even consider people who offer their organs to strangers crazy. Why would anyone do that? Who are these people so committed to helping others-strangers-that they would undergo surgery, discomfort, and disruption of their lives? This book profiles donors who have offered their organs to strangers and helps readers understand the meanings behind their donations. For the donor, altruism should always be the primary motivation, though other motivations often come into play. Often, there are also subconscious reasons for performing this great act of kindness. The Organ Donor Experience gives living anonymous organ donors of kidneys, liver lobes, and lung lobes the opportunity to tell their stories as they understand them, and for others to understand the motivations and the meaning of true altruism.